Undulators, Wigglers and their Applications - Onuki H. Hideo; Elleaume P. Pascal (London, Taylor & Francis, 2003)
Synchrotron radiation is the intense radiation over a broad spectral range produced by electrons or positrons in a bending magnet of a synchrotron or storage ring. The spectral range of this radiation can be concentrated around a few frequencies by 'wiggling' the electron (or positron) beam and the device used to produce this effect was originally called a wiggler. Many short amplitude wigglers in succession serve to concentrate the radiation spatially in a narrow cone, and spectrally in a narrow frequency interval. A multi-period wiggler such as this is called an undulator, and undulator and wiggler devices are generically known as insertion devices as they are inserted in a free straight section of a storage ring.This book contains a detailed presentation of the radiation produced by insertion devices, the engineering and the associated beamline instrumentation, and some scientific applications. Examples of the most important topics from a large variety of scientific fields including solid state physics, biology, biomedical systems, polarization modulation spectroscopy, optical engineering, and metrology are included, the intention being to stimulate the reader's interest in the many applications of insertion devices. This book will be of interest to a wide range of students, researchers, and engineers working in the field of synchrotron radiation.